2017
DOI: 10.1016/j.electacta.2017.03.166
|View full text |Cite
|
Sign up to set email alerts
|

Electrochromic Thin Films of the V-Cr Prussian Blue Analogue Molecular Magnet

Abstract: This paper describes spectroelectrochemical measurements of thin films of the V II/III -Cr III Prussian blue analogue (V-Cr PBA). We show that we can electrically control the optical properties of this room-temperature molecule-based magnet and reversibly switch the colour of the films from blue to black upon reduction. The cyclic voltammogram of the films showed a weak wave at −0.85 V and a stronger wave at −1.22 V. The spectroelectrochemical measurement in KCl indicate that the wave at −0.85 V is related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…In order to fit all the required electrodes for the spectroelectrochemical measurements into the cuvette, the SCE reference and counter electrode were replaced with Pt wire electrodes. A previous investigation 22 of this arrangement of electrodes showed that the use of the pseudo-reference results in a shift of less than 0.02 V with respect to the SCE arrangement. Cyclic voltammograms were carried out on each of the layers individually and the bilayer structure in order to determine switching potentials to be used during the spectroelectrochemistry.…”
Section: Introductionmentioning
confidence: 83%
“…In order to fit all the required electrodes for the spectroelectrochemical measurements into the cuvette, the SCE reference and counter electrode were replaced with Pt wire electrodes. A previous investigation 22 of this arrangement of electrodes showed that the use of the pseudo-reference results in a shift of less than 0.02 V with respect to the SCE arrangement. Cyclic voltammograms were carried out on each of the layers individually and the bilayer structure in order to determine switching potentials to be used during the spectroelectrochemistry.…”
Section: Introductionmentioning
confidence: 83%
“…[31] and references therein). Inspired by our recent spectroelectrochemical study on thin films of the V-Cr PBA [16], we have in this letter investigated if a similar approach would be feasible. In the spectroelectrochemical study, we found that a new optical absorption peak arises at ca.…”
Section: Fig 1: Static Transmission Spectrum Of the V-cr Pba The Lomentioning
confidence: 99%
“…The V-Cr PBA also displays interesting proton conductive [13], photomagnetic [14] and electrochromic [15,16] properties. There have been few ultrafast studies to date on PBAs in general [17][18][19][20][21][22] to probe the initial fs−ps dynamics after photoexcitation.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochromism lies in the variation of the optical properties consisting of the color, transparency, etc., when subjected to the electric charge . Giving the credit to the properties of high color contrast and low voltage consumption, electrochromic materials are potential for applications such as smart windows, rear‐view mirrors, information displays, electronic papers, and military camouflage . WO 3 was first reported as electrochromic material by Deb in 1969 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Giving the credit to the properties of high color contrast and low voltage consumption, electrochromic materials are potential for applications such as smart windows, rear-view mirrors, information displays, electronic papers, and military camouflage. [5][6][7][8] WO 3 was first reported as electrochromic material by Deb in 1969. 9 After that, various electrochromic materials including metal oxides, coordination complexes, small organic molecule, side-chain-substituted polymers, or main-chain fully conjugated polymers were reported.…”
Section: Introductionmentioning
confidence: 99%